The Effects and Unintended Consequences of the Sarbanes-Oxley Act on the Supply and Demand for Directors - Linck, James S.; Netter, Jeffry M.; Yang, Tina (Review of Financial Studies, 2009)
Using 8,000 public companies we study the impact of the Sarbanes-Oxley Act (SOX) and other contemporary reforms on directors and boards, guided by their impact on the supply and demand for directors. SOX increased director workload and risk (reducing the supply), and increased demand by mandating that firms have more outside directors. We find both broad-based changes and cross-sectional changes (by firm size). Board committees meet more often post SOX and Director and Officer (D&O) insurance premiums doubled. Directors post SOX are more likely to be lawyers/consultants, financial experts and retired executives, and less likely to be current executives. Post-SOX boards are larger and more independent. Finally, we find significant increases in director pay and overall director costs, particularly among smaller firms.?